Pengaruh Kualitas Sistem IoT Forest Fire dalam Mendeteksi Kebakaran Hutan Terhadap Kepuasan Pengguna - Alkautsar, Muhammad Farhan; Rahmah, Hikmah; Aziezah, Nur (Jurnal Teknik Komputer dan Informatika, 2023)
The objective of this study is to see the great impact of the quality of Forest Fire IoT system in forest fire detection on user satisfaction and also provide information from the analysis results for the development of Forest fire IoT systems to improve user satisfactions. A quantitative approach with a correlational type will be used to test the relationship of variables to the subject being studied more causally. This research has found that the system quality variables on Forest Fire IoT system devices as forest fire detectors have a positive and significant impact on user satisfaction. The better the quality of the system is made, the greater the satisfaction perceived by the user.